Thermal comfort in outdoor spaces: Street markets in Presidente Prudente, Brazil - Hamanaka, Bruna [UNESP]; Bueno-Bartholomei, Carolina Lotufo [UNESP] (My University, 2017)
The objective of this paper was to verify the influence of tree shades on the thermal sensation of workers and users that perform different activities (work or leisure) in three street markets in Presidente Prudente (Brazil), in the summer period. The methodology consisted of microclimatic monitoring (air temperature, relative humidity, air velocity and global radiation) and the application of questionnaires to workers and users to determine the thermal sensation and their personal parameters (age, gender, height, weight, clothing and metabolism). Through the collected data, it was possible to define the calculated thermal comfort and to compare it with the actual thermal comfort. For this purpose, we used the Universal Thermal Climate Index (UTCI) and the Actual Sensation Vote (ASV). Although the two groups performed different activities, the results show that most of them were comfortable regardless of the interview location (sun or shade). Furthermore, the UTCI index did not present satisfactory results for Presidente Prudente city, which demonstrates the need for adjustment in the model.
Keywords: ASV; Open markets; Thermal comfort; Urban forestry; UTCI